The antidepressant-like effects of kisspeptin-10 are reversed by kisspeptin antagonist peptide 234 in male rats: Kisspeptin-10's antidepressant effects in male rats - Serhatlioglu, Ihsan; Kacar, Emine; Yardimci, Ahmet; Ulker Ertugrul, Nazife; Bulmus, Ozgur; Ercan, Zubeyde; Kelestimur, Haluk (Cellular and Molecular Biology, 2024)
Kisspeptins are reported to be the most potent activators of the hypothalamus-pituitary-gonadal (HPG) axis known to date. Kisspeptin potently elicits gonadotropin-releasing hormone (GnRH) release and luteinizing hormone (LH) secretion, even in the pre-pubertal period. Beyond the hypothalamus, kisspeptin is also expressed in limbic and paralimbic brain regions, which are areas of the neurobiological network primarily implicated in emotional behaviors alongside sexual functions. Therefore, an increasing body of studies has implicated kisspeptin as having many influences on emotional behaviors. The study was set out to explore if the kisspeptin/GPR54 signaling system is required for the anti-depressant-like effect of kisspeptin-10 (KP-10), besides the regulation of the HPG axis. To test this concept, peptide 234 (P234), a kisspeptin antagonist, was given to the male rats, and its modulatory effect on the anti-depressant-like effects of kisspeptin was investigated by using a forced swimming test (FST). The study has also sought to know whether kisspeptin can exert its effects through adrenergic and serotonergic receptors. To investigate this, the agents yohimbine (Yoh), an alpha-2 adrenergic receptor antagonist, and cyproheptadine (Cry), a non-selective 5-HT2 serotonergic receptor antagonist, were administered in the experiments. Our results indicate that, in rats, the anti-depressant-like effects of KP-10 in a modified rat FST are mediated by GPR54 receptors, since the kisspeptin antagonist peptide 234 reversed kisspeptin-induced anti-depressant-like effects. Our data also demonstrate that the anti-depressant-like effects of kisspeptin, at least in part, are mediated by an interaction of the alpha-2 adrenergic and 5-HT2 serotonergic receptors.